Agriculture and youth in Nigeria: Aspirations, challenges, constraints, and resilience - ElDidi, Hagar; Bidoli, Thomas; Ringler, Claudia (International Food Policy Research Institute, 2020)
Nigeria’s rural youth are facing various challenges in agriculture, with limited job opportunities outside the sector. Using qualitative focus group discussions and individual interviews with youth in four communities in two Nigerian states, the paper reflects on nuanced differences in perceptions of opportunities, coping mechanisms and overall resilience of youth in rural Nigeria, as well as differential access to information, inputs and irrigation based on age, gender and community. We apply the GCAN framework, to illustrate the factors that shape resilience pathways in the context of climate change and other shocks and stressors. Many of the constraints rural youth face are faced by other groups, including lack of finance, farm inputs and modern equipment for production and processing. Yet, youth face higher and specific hurdles related to lack of capital, experience and a strong social capital and networks that would facilitate coping with climatic and other shocks and improving their livelihoods. Young women in particular have less access to information and irrigation, and are less likely to benefit from cooperative memberships. Nevertheless, young men and women have higher resilience compared to older groups in terms of health, mobility and ability to migrate, as well as easier access to the internet as a source of information. Youth can better build resilience and a network and receive government assistance when part of a cooperative. Nevertheless, a larger enabling environment in the sector is needed, to improve roads, access to markets, information, inputs and equipment to support young farmers who cannot leave the agriculture sector. A promising factor is that many young men and women realize the importance of agriculture and aspire to become successful in the sector.